Short-term outcomes of fetoscopic laser surgery for severe twin-twin transfusion syndrome from Taiwan single center experience: Demonstration of learning curve effect on the fetal outcomes - Yao-Lung Chang; An-Shine Chao; Shuenn-Dyh Chang; Peter C.C. Hsieh; Chao-Nin Wang (Elsevier, 2012)
Objective: To evaluate the learning curve effect on fetal outcomes while using fetoscopic laser photocoagulation (FLP) for twin-twin transfusion syndrome (TTTS) as managed by a newly established single center in Taiwan. Materials and Methods: Between October 2005 and October 2010, women diagnosed to have TTTS before 26 weeks of gestation were offered FLP surgery. Cases were divided into first-half and second-half groups to evaluate the learning effect on fetal outcomes including at least one survival rate, two survival rate, and gestational age of delivery. Results: A total of 44 cases with a median gestational age of 20.1 weeks (range 16-25) at operation were included in the study. Overall, both twins survived in 22 (50.0%) cases, whereas only one twin was born alive in 13 (29.5%), and neither was born alive in the remaining nine cases (20.5%). The total survival rate was 64.8%. When comparing the first-half 22 cases and the second-half 22 cases, there were significant improvements in total survival rate (54.7% vs. 75.0%, p = 0.045), a prolonged interval between operation and delivery (62.1 vs. 89.1 days, p = 0.042), and more advanced gestational age of delivery (28.3 vs. 33.0 weeks, p = 0.008) in the second-half 22 cases. Conclusions: With increasing experience in using fetoscopic guide laser therapy for TTTS, the fetal survival rate could be improved with advanced gestational age at delivery.